The Role of Living Arrangements and Parental Marital Status on Adolescent Self-Efficacy in Preventing Risky Sexual Behavior - Pipit Feriani; Wahyuni, Tri; Selpina; Nur’ Aini Permatasari; Khofifah Yuniarsih Sadri; Syarah Auliza Firdayanti Yunus (Health & Medical Sciences, 2026)
This study aims to analyze the role of living arrangements and parental marital status in shaping adolescent self-efficacy for premarital sex prevention through a Health Belief Model (HBM) framework. Using a quantitative cross-sectional design at SMAN 3 Samarinda (n=301), data were analyzed to determine how family structural dynamics influence internal confidence. Results indicate a significant relationship between living arrangements (p=0.002) and parental marital status (p=0.001) with self-efficacy. High family support shows a strong positive correlation with perceived susceptibility (r=0.766) and health motivation (r=0.756), ultimately driving self-efficacy (r=0.812). Adolescents in intact families and those living with parents demonstrate higher resilience against risky sexual behaviors. This study concludes that family environmental stability is a critical "Cue to Action" in adolescent reproductive health.